Big star fallin' mama : five women in Black music - Jones, Hettie (New York, N.Y., U.S.A. : Viking, 1995)
Portraits of five Black women and the kind of music they sang during a period of social change. Includes Ma Rainey, Bessie Smith, Mahalia Jackson, Billie Holiday, and Aretha Franklin.
Keywords: African American women musicians -- Juvenile literature; Blues (Music) -- History and criticism -- Juvenile literature; Musicians; African Americans -- Biography; Blues (Music)